Василь Стефаник у Чехії: прижиттєва критична й перекладна рецепція - Будний, В. (Слово і Час, 2022)
У статті досліджено тематичні й жанрові виміри процесу сприймання творчості прозаїка. З’ясовано, що відкривавчі статті І. Франка в місячнику «Slovanský přehled», перші переклади Стефаникових новел і полемічне зіткнення навколо них Ф. Кс. Шальди та Ст. К. Неймана поклали початок зацікавленому та плідному освоєнню новелістики українського митця. Окреслено жанровий спектр чеської стефаникіани (переклад, журнальна критика, наукові, освітні й довідкові видання) і коло письменників, перекладачів, літературознавців, які її розбудовували, оприлюднюючи результати своєї творчої праці в періодиці та книжкових публікаціях. The paper traces the perception of Vasyl Stefanyk’s works in Czechia, from the first mention of him by Ivan Franko in the monthly “Slovanský přehled” in 1898 to the obituaries of the writer, who passed away at the end of 1936. The research outlines the genre spectrum of Czech publications concerning Stefanyk’s works (translations; reviews in periodicals; scholarly, educational, and reference editions) and the circle of authors that paid attention to Stefanyk’s writings. In particular, it specifies the authorship of A. Proházka’s and V. Prach’s works assigned by cryptonyms. Stefanyk’s writings aroused the interest of the authors representing various literary directions and groups: Czech Modernism (František Šalda), the decadent periodical “Moderní revue” (Arnošt Proházka), a group of anarchist rebels (Stanislav K. Neumann), and the Masaryk’s movement of ‘realists’. The decadents and ‘rebels’ even showed a special affection for the Ukrainian author, as they were the first to translate him in their magazines and published the writer’s earliest and most complete lifetime Czech collection “Povídky” (“Stories”) in 1905. There were five Stefanyk’s books published in the writer’s homeland during his lifetime, but the biggest attention of the Czech translators was drawn to the collection “The Little Blue Book”, and among the short stories — “The News”, “He Committed a Suicide”, “Maple Leaves”, and “My Word”. Among well-known translators were Karel Rypáček, Jaroslav Rozvoda, and Rudolf Hůlka. Alois Koudelka, Jan Máchal, Vincenc Charvát published critical works exploring the expressionist style and existential issues of Stefanyk’s works. Czech critics oft en took guidance from the discourse on Stefanyk represented by I. Franko, B. Lepkyi, and Lesia Ukrainka. Perception of Stefanyk’s writings developed into an engaging study of the writer’s works in the institutionally branched and aesthetically differentiated cultural environment of Czechia in the interwar 20th century. This interest helped to establish a closer Czech-Ukrainian literary dialogue.